2009
DOI: 10.1530/eje-09-0202
|View full text |Cite
|
Sign up to set email alerts
|

Sex hormone-binding globulin predicts the incidence of hyperglycemia in women: interactions with adiponectin levels

Abstract: Objective: Previous evidence has suggested that a low sex hormone-binding globulin (SHBG) concentration is associated with insulin-resistance and a low adiponectin concentration. We investigated the association between SHBG and the risk of hyperglycemia in each sex and we determined potential interactions between SHBG and adiponectin levels in the development of dysglycemia. Design: We used a nested case-control design in the large prospective study, Data from an Epidemiological Study on the Insulin Resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 20 publications
5
32
0
Order By: Relevance
“…However, a few studies have reported that serum SHBG concentrations are also inversely correlated with HbA1c and FPG in both men and women without diabetes (13,15,26), suggesting a relationship between SHBG and glucose homeostasis before the development of diabetes. However, we did not find such a relationship in patients with T2D in this study, which is consistent with the finding of no correlation between blood glucose and HbA1c with serum SHBG in type 1 diabetes (T1D) patients (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a few studies have reported that serum SHBG concentrations are also inversely correlated with HbA1c and FPG in both men and women without diabetes (13,15,26), suggesting a relationship between SHBG and glucose homeostasis before the development of diabetes. However, we did not find such a relationship in patients with T2D in this study, which is consistent with the finding of no correlation between blood glucose and HbA1c with serum SHBG in type 1 diabetes (T1D) patients (27).…”
Section: Discussionmentioning
confidence: 99%
“…This concept is supported by an in vitro experiment in which human HepG2 hepatoblastoma cells produce less SHBG when treated with insulin (11,12). However, a few of the subsequent studies have found no direct association between SHBG and insulin or insulin resistance (13,14,15). A recent study by Selva et al (16) reports that SHBG is not regulated by insulin but rather repressed by monosaccharide-induced lipogenesis in human HepG2 cells.…”
Section: Introductionmentioning
confidence: 97%
“…Several cross-sectional and prospective studied observed low levels of testosterone in men and high levels of bioavailable testosterone in women with T2DM 24,25,26 , and that testosterone level is not affected by the menopause state in women 27 . Additionaly, diabetic premenopausal women with normal body weight show higher levels of free testosterone compared to healthy premenopausal women of matched body weight.. Also, non-diabetic obese women showed the higher free testosterone level than levels estimated in non-diabetic non-obese premenopausal women 28 .…”
Section: Discussionmentioning
confidence: 98%
“…In a 3 years prospective study, Bonnet et al agreed that the SHBG was significantly associated with hyperglycemia and was negatively correlated with HOMA-IR and fasting insulin 26 . Moreover, Onat et al found a negative correlation between SHBG and HOMA-IR, fasting glucose level and thus inversely correlated with insulin resistance 43 , and this inverse correlation was stronger in premenopausal women than in postmenopausal 44 .…”
mentioning
confidence: 98%
“…Evidence suggests that hyperinsulinemic insulin resistance may increase serum levels of ovarian androgens and reduce sex hormone-binding globulin (SHBG) levels in women. Reasoned opinions are, therefore, that a low SHBG level is a strong risk marker for dysglycemia in women, independently of both adiponectinemia and insulinemia (Bonnet et al, 2009). SHBG may therefore improve the identification of women at risk of diabetes.…”
Section: Pcos Laboratory and Sonographic Evaluationmentioning
confidence: 99%